REVITALISASI œMELEK-MELEKAN SEBAGAI KEARIFAN LOKAL BATAK TOBA YANG TERABAIKAN - sitanggang, martua reynhat (CULTURAL EDUCATION JOURNAL OF LITERATURE AND CULTURE, 2022)
This research certainly has goals to be achieved, among others: to revitalize œliteracy, as the neglected local wisdom of Batak Toba. In this study, it is limited to the revitalization of literacy in the city of Medan. Cultural revitalization is the realignment of local cultural values which may have many deviations among cultural adherents, these deviations can be viewed from the perspective of religion, social, education, economy and society, so that the existence of this culture is not one of the parties on the one hand. and benefit the other side. The most appropriate method used is descriptive qualitative. Qualitative descriptive method is a research method based on the philosophy of postpositivism which is usually used to examine natural objective conditions in which the researcher acts as a key instrument. And Research Results A form of literacy activity has been carried out in the house of one of the residents. The point is to socialize and revitalize the literacy tradition.